1999
DOI: 10.1597/1545-1569(1999)036<0450:dgiibb>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Dentoalveolar Growth Inhibition Induced by Bone Denudation on Palates: A Study of Two Isolated Cleft Palates with Asymmetric Scar Tissue Distribution

Abstract: Analysis via flowmetry showed that the palatal scar tissue area was limited to the anterior tooth region on the right (unaffected) side but extended posteriorly to the premolar region on the left (affected) side in both subjects. The two girls had similar dentoalveolar structures, with the dental and alveolar arches deflected lingually at the deciduous molar area on the affected side. There were no differences in the buccolingual inclination of deciduous molars or in the vertical growth of the alveolar process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Ross 3,4 suggested that postsurgical scar tissue induced the periodontal ligament to pull anterior teeth backward toward the palate. Smahel et al 2 and Ishikawa et al 5 described that the lingual inclination of the dentoalveolar process on the cleft side was a result of periosteal denudation of the bone and its scar tissue. Wijdeveld et al, 23 in their histologic studies on beagle dogs, showed that the scar tissue covering denuded bone on lateral sides of the palate were mainly transversally orientated collagenous fibers that lacked blood supply and elastic fibers and had a continuation with the periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ross 3,4 suggested that postsurgical scar tissue induced the periodontal ligament to pull anterior teeth backward toward the palate. Smahel et al 2 and Ishikawa et al 5 described that the lingual inclination of the dentoalveolar process on the cleft side was a result of periosteal denudation of the bone and its scar tissue. Wijdeveld et al, 23 in their histologic studies on beagle dogs, showed that the scar tissue covering denuded bone on lateral sides of the palate were mainly transversally orientated collagenous fibers that lacked blood supply and elastic fibers and had a continuation with the periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…The permanent central incisor is palatally inclined, [1][2][3][4] while the deciduous canine and deciduous molars are palatally inclined or displaced along with palatal collapse of the maxillary lateral segment. 5 Numerous studies of maxillary dental arch dimension in UCLP at different ages have shown significantly smaller than normal maxillary arch width and length. [6][7][8][9][10][11] While studies have described arch contraction in different regions of the arch in UCLP, maxillary arch width differences between the cleft and noncleft sides have been rarely discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Ross and Johnston 2 suggested that postsurgical scar tissue induced the periodontal ligament to pull anterior teeth backward and rotated toward the palate. Ishikawa et al 15 described that the lingual inclination of the dentoalveolar process on the cleft side was a result of periosteal denudation of the bone and its scar tissue. Smahel et al 3 suggested that rotation of incisors could be a result of a lack of space at the end of the alveolar segment and might be associated with other factors such as absence of the lateral incisor and an anomaly of the dental anlage.…”
Section: Discussionmentioning
confidence: 99%
“…Another indication of LDF is in monitoring pulpal reactions to orthodontic procedures (McDonald & Pitt Ford 1994, Barwick & Ramsay 1996, Brodin et al. 1996, Ishikawa et al. 1998, 1999, Ikawa et al.…”
Section: Indicationsmentioning
confidence: 99%